Analisis Perbandingan Kuantitas Batubara Antara Drone Dji Phantom 4 RTK Dengan Terrestrial Laserr Scanner Pada Stockpile LS DH5: Comparative Analysis of Coal Quantity Between DJI Phantom 4 RTK Drone and Terrestrial Laser Scanner on LS DH5 Stockpile - Hardianti, Siti; Maryana; Dilariya (MINERAL, 2025)
Calculation of coal quantity can be done by various methods, one of which is by measuring the detailed situation using survey tools such as Total Station, GPS or GNSS, can also use Terrestrial Laser Scanner and popular technology currently used for volumetric survey activities is unmanned aircraft or drones. The purpose of this study was to determine the quantity of coal stockpile LS DH 5 using the DJI Phantom 4 RTK Drone and Terrestrial Laser Scanner, compare the quantity results of the two measuring instruments and determine the feasibility of the coal quantity measured by the DJI Phantom 4 RTK Drone against the quantity measured by the Terrestrial Laser Scanner. The calculation results using the DJI Phantom 4 RTK Drone were 243,214.506 tons and the calculation results using the Terrestrial Laser Scanner were 242,713.028 tons, between the two calculations there was a difference of 501.478 tons or 0.21%, From this comparison, the calculation results of the DJI Phantom 4 RTK Drone are considered close to accuracy because they are within the tolerance standard (Industry Adapted Error) used, which is 2% according to ASTM D6172-98.